From Coordination to Integration: Explaining Flood Governance Performance in Greater Jakarta’s Ciliwung-Cikeas-Cisadane Watersheds - Rahmat Salam; Izzatusholekha; Tria Patrianti; Nur Muhamad Iqbal (Publica: Jurnal Pemikiran Administrasi Negara, 2026)
This study examines why flood control efforts in Greater Jakarta consistently underperform despite substantial investments and formal coordination mechanisms. Focusing on the Ciliwung, Cikeas, and Cisadane watersheds, it assesses an integrated governance approach framed as "One River, One Planning, One Integrated Management." The study analyzes survey data from 350 residents across seven flood-affected areas using an explanatory sequential mixed-methods design, with coordination capacity, policy integration, and flood governance effectiveness measured through Likert-scale indicators and tested via hierarchical regression and mediation analysis. The quantitative results show that coordination capacity is positively associated with perceived flood governance effectiveness, but its effect declines when policy integration is introduced, indicating a strong mediating role of integration. To explain these patterns, the qualitative phase draws on interviews with environmental agency leadership, a multi-stakeholder focus group discussion, field observations, and policy document review, analyzed through NVivo thematic coding. Five mechanisms consistently explain the integration gap: mandate overlap and organizational silos, spatial planning misalignment, financing and operations–maintenance discontinuities, weak enforcement combined with risk-amplifying public behaviors, and limited interoperability of data and early warning systems.